Phase Transition Process of Graphite to Diamond Induced by Monodispersed Tantalum Atoms at Ordinary Pressure - Zhiguang Zhu; Chengke Chen; Shaohua Lu; Xiao Li; Xiaojun Hu (Advanced Science)
Abstract The transformation of graphite into diamond (2–10 nm) at ordinary pressure by monodispersed Ta atoms was recently reported, while the effects of Ta concentration on the transition process remain obscure. Here, by regulating the Ta wire treatment time, as well as the annealing time and temperature, larger diamond grians (5–20 nm) are successfully synthesized, and the transition process of graphite to diamond is revealed to vary with Ta concentration. Specifically, short Ta wire treatments (5–10 min) induce graphite to form a “circle” structure and transforms into diamond directly after annealing. Long Ta wire treatments (15–25 min) produce larger and more “circle” structures, containing an increased number of graphite layers. After annealing at 1100 °C for 30–120 min, graphite first transforms into amorphous carbon, then to i‐Carbon and n‐Diamond, and finally to diamond. Notably, a large amount of n‐Diamond and diamond are formed after 120 min annealing. By modulating the annealing temperature from 500 to 1200 °C for 30 min, diamond is already obtained at 500 °C, and hexagonal diamond up to 20 nm in size at 1200 °C. This provides a fresh insight into the graphite/diamond transition process and an approach for diamond synthesis.